Revealing the internal luminescence quantum efficiency of perovskite films via accurate quantification of photon recycling - Faßl, Paul; Lami, Vincent; Berger, Felix J.; Falk, Lukas M.; Zaumseil, Jana; Richards, Bryce S.; Howard, Ian A.; Vaynzof, Yana; Paetzold, Ulrich Wilhelm (Matter, 2021)
The internal luminescence quantum efficiency (Qilum) provides an excellent assessment of the optoelectronic quality of semiconductors. To determine Qilum from the experimentally accessible external luminescence quantum efficiency (Qelum), it is essential to account for photon recycling, and this requires knowledge of the photon escape probability (p¯e). Here, we establish an analysis procedure based on a curve-fitting model that accurately determines p¯e of perovskite films from photoluminescence (PL) spectra measured with a confocal microscope and an integrating sphere setup. We show that scattering-induced outcoupling of initially trapped PL explains commonly observed red-shifted and broadened PL spectral shapes and leads to p¯e being more than a factor of two higher compared with earlier assumptions. Applying our model to CH3NH3PbI3 films with exceptionally high Qelum up to 47.4% corrects previous estimates for Qilum of ∼90% to a real benchmark of 78.0% ± 0.5%. Thereby, our study reveals there is beyond a factor of two more scope for reducing non-radiative recombination in perovskite films than previously thought.
Gesehen am 09.06.2021